Ontogeny and reproductive functional morphology of the macroalga Wiartonella nodifera n. gen. n. sp. (Dasycladales, Chlorophyta) from the Silurian Eramosa Lagerstätte of Ontario, Canada. (28th November 2016) - LoDuca, Steven T.; Tetreault, Denis K.
Abstract: The thallus of a new noncalcified dasycladalean alga, Wiartonella nodifera n. gen. n. sp., from the mid-Silurian Eramosa Lagerstätte of Ontario, Canada, comprises a narrow main axis with laterals in whorls (euspondyl). Laterals branch to the second order and show a distinct expansion (node) at the termination of first-order lateral segments. Morphologic differences between specimens are interpreted as ontogenetic stages similar to those displayed by extant Dasycladales, including late-stage shedding of higher-order lateral segments. Examination of reproductive functional morphology using biophysical modeling indicates that the expanded terminations of the first-order lateral segments probably are not homologous with gametophores, and that reproduction instead was either endospore or cladospore, with details of the ontogenetic sequence pointing to the latter. The distinctive lateral morphology displayed by this species adds to the list of morphological innovation achieved by dasycladalean algae during a significant burst of evolutionary activity that unfolded between the Middle Ordovician and late Silurian.